Temperature-dependent vibration energy harvesting performance of polyimide/(Na, K)NbO3 piezoelectric composites. (1st November 2022) - Yamamoto, Ryota; Hegendörfer, Andreas; Mergheim, Julia; Kakimoto, Ken-ichi
Abstract: A composite structure of piezoelectric particles and soft polymer composite material is one of the candidates that converts environmental vibration energy into electrical energy. Presently, expanding the usage of applications is needed in terms of the working environment at harsh temperatures. Polyimide is flexible and temperature-stable polymer. In this research, we report a synthesis of polyimide/(Na, K)NbO3 (PI/NKN) flexible composites. We constructed a setup, where vibration and heat are simultaneously applied to the PI/NKN composites. The frequency and temperature dependence of the output voltage were investigated at room temperature up to 200 °C. Relative permittivity, piezoelectric constant, and output voltage of the PI/NKN showed temperature stability. Flexibility and glass transition temperature of a polymer matrix are important factors. PI/NKN composites are potential energy harvesting materials with flexibility and excellent high-temperature stability.